Patients with Systemic Lupus Erythematosus Show Increased Levels and Defective Function of CD69+ T Regulatory Cells - Marlen Vitales-Noyola; Brenda Oceguera-Maldonado; Perla Niño-Moreno; Nubia Baltazar-Benítez; Lourdes Baranda; Esther Layseca-Espinosa; Carlos Abud-Mendoza; Roberto González-Amaro (Mediators of Inflammation)
T regulatory (Treg) cells have a key role in the pathogenesis of chronic inflammatory and autoimmune diseases. A CD4+CD69+ T cell subset has been described that behaves as Treg lymphocytes, exerting an important immune suppressive effect. In this study, we analyzed the levels and function of CD4+CD69+ Treg cells in patients with systemic lupus erythematosus (SLE). Blood samples were obtained from 22 patients with SLE and 25 healthy subjects. Levels of CD4+CD69+ Treg cells were analyzed by multiparametric flow cytometry, and their function was measured by an assay of suppression of lymphocyte activation and through the inhibition of cytokine synthesis. We found an increased percent of CD4+CD25varCD69+TGF-β+IL-10+Foxp3− lymphocytes in patients with SLE compared to controls. In addition, a significant diminution in the suppressive effect of these cells on the activation of autologous T lymphocytes was observed in most patients with SLE. Accordingly, CD69+ Treg cells from SLE patients showed a defective capability to inhibit the release of IL-2, IL-6, IL-10, and IL-17A by autologous lymphocytes. Our findings suggest that while CD4+CD69+ Treg lymphocyte levels are increased in SLE patients, these cells are apparently unable to contribute to the downmodulation of the autoimmune response and the tissue damage seen in this condition.